Diversifikasi Olahan Sayuran dan Buah oleh Kelompok Wanita Tani Koperasi Sinergi Kampung Domba, Kabupaten Cirebon - Alina Hizni; Sholichin, Sholichin; Samuel, Samuel (Institut Pertanian Bogor, 2024)
The Covid-19 pandemic has impacted the increasing consumption of vegetables and fruit because they contain lots of vitamins and minerals to increase endurance. The purpose of community service activities is to diversify processed vegetables and fruits to increase selling value. The activity's target is to improve vegetable and fruit processing skills. The output of the activity is the diversification of processed vegetables and fruit. The target of the activity is women farmers who are members of the Kampung Domba Synergy Cooperative. Stages of activity include: 1). The preparatory stage, namely the manufacture of vegetable and fruit processing modules; 2). The implementation phase, namely vegetable and fruit processing training; 3). Evaluation Phase, in the form of pre-test and post-test related to knowledge of processing vegetables and fruit. Community service activities in collaboration with the Kampung Domba Synergy Cooperative (SiKado) and the Cirebon Regency Agricultural Institute Alumni Association (HA IPB). Community service activities were carried out for two days. The first day's activity was the presentation of material on the development of the food product business by the Alumni Association of IPB Cirebon Regency, followed by the presentation of material on the design of food product packaging by the Kampung Domba Synergy Cooperative and material on the processing of vegetables and fruit by the Community Service Team. Based on the pre-test and post-test on the participants' knowledge of vegetable and fruit processing, the average score was 78.0 (fair category) and 84.1 (good category), respectively, with an increase of 6.1 points. The second day's activity was training in processing and evaluating the preferences of processed fruit and vegetable products, and 71.4% of the products (5 out of 7 products) received an overall rating of 4 (liked) by the panelists, namely es puter cucumber suri, spinach sticks, kale sticks, corn tortillas and candied kolang kaling.